A contribution to the herpetology of Bako national park, Sarawak, East Malaysia - Das, I.; Charles, Joseph K. (Centre for Herpetology, Madras Crocodile Bank Trust, 1993)
The paper lists 20 species of amphibians and reptiles recorded thus far from Bako National Park, Sarawak, East Malaysia, based on field observations, published information and material collected by the Park authorities. At present, the known herpetofauna consists of one amphibian, eight lizards and eleven snake species. It is anticipated that the total number of species found in the area will grow considerably with sampling effort.